2013
DOI: 10.1002/ejlt.201200429
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous metal complex catalyzed conjugation of methyl linoleate

Abstract: Conjugated methyl linoleates (CML) can be produced by homogeneous transition metal catalysis under mild reaction conditions, low catalyst concentrations and short reaction times in nearly quantitative yield from methyl linoleate (ML), an easily accessible intermediate product of the oleochemical industry. The best catalyst proved to be the Wilkinson-catalyst RhCl(PPh 3 ) 3 (1 mol%) activated by the co-catalyst tin(II)chloride-dihydrate (2.5 mol%) in the solvent methanol. A yield of 93% of conjugated methyl lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…, CH --CH); 3.69 (s, 6H, 2ÂCHCOOCH 3 ); 3.66 (s, 3H, CH 2 COOCH 3 ); 3.08 (d, 2H, 2 J HH ¼ 6.5 Hz, 2ÂCHCOOCH 3 ) 2.41-2.43 (m, 2H, 2xCHCH 2 ); 2.29 (t, 2H, 3 J HH ¼ 7.4 Hz, CH 2 COOCH 3 ); 1.57-1.63 (qui, 2H, 3 J HH ¼ 7.4 Hz, CH 2 CH 2 COO); 1.26-1.52 (m, 20H, 10ÂCH 2 ); 0.88 (t, 3H, 3 J HH ¼ 6.9 Hz, CH 2 CH 3 ); 13 (17); 378 (6); 346 (94); 328 (22); 318 (22); 296 (4); 287 (29); 279 (55); 269 (12); 247 (100); 233 (17); 215 (13); 203 (14); 189 (42); 175 (10); 145 (61); 119 (11); 113 (37); 105 (34); 91 (31); 79 (14); 69 (15); 55 (28); 43 (21); syn-Trimethyl-3-octyl-(E)-undec-4-ene-1,2,11-tricarboxylate (5a) and syn-Trimethyl-(E)-3-(non-1-ene-1-yl)decane-1,2,10-tricarboxylate(6a) [1,2] : 1 (10); 348 (93); 335 (25); 316 (25); 303 (15); 294 (14); 265 (11); 263 (11); 247 (12); 219 (12); 205 (15); 189 (9); 175 (7); 161 (7); 149 (13); 146 (100); 135 (11); 121 (14); 114 (37); 97 (20); 95 (23); 81 (30); 67 (30); 55 (41); 44 (30); anti-Trimethyl- We have previously reported on the maleinisation of linoleic acid [26], where we found that Rh(OAc) 2 shows a higher activity and leads to higher yields compared to RhCl 3 (H 2 O) 3 . The same tendency was found for 2, which is consistent with the results of Behr and Handwerk [28].…”
Section: Isomerization Of Double Bond Configurationmentioning
confidence: 99%
“…, CH --CH); 3.69 (s, 6H, 2ÂCHCOOCH 3 ); 3.66 (s, 3H, CH 2 COOCH 3 ); 3.08 (d, 2H, 2 J HH ¼ 6.5 Hz, 2ÂCHCOOCH 3 ) 2.41-2.43 (m, 2H, 2xCHCH 2 ); 2.29 (t, 2H, 3 J HH ¼ 7.4 Hz, CH 2 COOCH 3 ); 1.57-1.63 (qui, 2H, 3 J HH ¼ 7.4 Hz, CH 2 CH 2 COO); 1.26-1.52 (m, 20H, 10ÂCH 2 ); 0.88 (t, 3H, 3 J HH ¼ 6.9 Hz, CH 2 CH 3 ); 13 (17); 378 (6); 346 (94); 328 (22); 318 (22); 296 (4); 287 (29); 279 (55); 269 (12); 247 (100); 233 (17); 215 (13); 203 (14); 189 (42); 175 (10); 145 (61); 119 (11); 113 (37); 105 (34); 91 (31); 79 (14); 69 (15); 55 (28); 43 (21); syn-Trimethyl-3-octyl-(E)-undec-4-ene-1,2,11-tricarboxylate (5a) and syn-Trimethyl-(E)-3-(non-1-ene-1-yl)decane-1,2,10-tricarboxylate(6a) [1,2] : 1 (10); 348 (93); 335 (25); 316 (25); 303 (15); 294 (14); 265 (11); 263 (11); 247 (12); 219 (12); 205 (15); 189 (9); 175 (7); 161 (7); 149 (13); 146 (100); 135 (11); 121 (14); 114 (37); 97 (20); 95 (23); 81 (30); 67 (30); 55 (41); 44 (30); anti-Trimethyl- We have previously reported on the maleinisation of linoleic acid [26], where we found that Rh(OAc) 2 shows a higher activity and leads to higher yields compared to RhCl 3 (H 2 O) 3 . The same tendency was found for 2, which is consistent with the results of Behr and Handwerk [28].…”
Section: Isomerization Of Double Bond Configurationmentioning
confidence: 99%
“…Therefore, this work further exhibited the significant role of Lewis acid properties, rather than the redox properties, of the Cu(II) cation in promoting Pd(II)-catalyzed olefin isomerization. Remarkably, the isomerizations were conducted under air in the present studies, whereas previously reported olefin isomerizations were generally conducted under N 2 or Ar [21][22][23], which highlights the merit of the catalyst system demonstrated here. In 1 H NMR characterizations of ML substrate and CML products, the chemical shift observed at 2.7-2.8 ppm is known as the methylene protons positioned between the two C=C bonds in ML as shown in Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Using methyl linoleate (ML) as a vegetable oil model, a series of non-redox metal ions were tested as Lewis acids to promote simple Pd(OAc) 2 catalyzed olefin isomerization in toluene/t-BuOH at 110 °C, and the results are summarized in Table 1. In the literature, the reported catalysts for efficient vegetable oil isomerization include Ru-and Rhbased metal complexes with phosphine ligands like PPh 3 , while a Pd-based catalyst was not reported [19][20][21][22][23][24][25][26]; even in common olefin isomerization, the reported Pd catalysts were less active than those that were Ru or Rh based [36]. As shown in Table 1, Pd(OAc) 2 alone as a catalyst is also inactive for the transformation of ML to its conjugated methyl linoleates (CML).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another option for the large scale production of CLAs starts from ricinoleic acid [13][14][15]. Besides, there are also investigations on the transition-metal catalysed isomerisation of fatty acids which can be carried out homogeneous [16,17] or heterogeneous [18,19]. Another alternative is the use of microorganism [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%